Participatory procurement practice of water sector in foreign aided project: an analysis of ADB finance "SWAIWRPMP project" in BWDB - Das, Amrita Kumar (BRAC University, 2014)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2013.